The upper limit of physiological cardiac hypertrophy in elite male and female athletes in China - Sun, B.; Ma, J. Z.; Yong, Y. H.; Lv, Y. Y. (European Journal of Applied Physiology, 2007)
Physiological hypertrophy in response to physical training is important in the differentiation of physiological and pathological left ventricular hypertrophy. The goal of our study was to define the structural characteristics of the heart in Chinese athletes. Between June 2005 and August 2005, 339 (165 male, 174 female) elite Chinese athletes from 19 sports were profiled. Standard two-dimensional guided M-mode and Doppler echocardiography were employed to evaluate left ventricular morphology and function. Of the 165 male athletes, 19 (11.5%) male athletes presented with an LVIDd = 60 mm, with an upper limit of 65 mm. Only three male athletes presented with wall thickness values =13 mm. Eighteen (10.3%) female athletes presented with an LVIDd = 50 mm, and seven (4.2%) female athletes presented with an LVIDd = 55 mm, with an upper limit of 62 mm. None were found to have a maximum wall thickness greater than 11 mm. Systolic and diastolic functions were within normal limits for all athletes. Results from the present study suggest that upper normal limits for left ventricular wall thickness and LVIDd are 14 and 65 mm for elite male Chinese athletes, and 11 mm and 62 mm for elite female Chinese athletes. Values in excess of these should be viewed with caution and should prompt further investigation to identify the underlying mechanism for the observed left ventricular hypertrophy.